2016
DOI: 10.1021/acsami.5b10404
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Porosity and Electrolyte Composition on the Surface Charge of Hydroxyapatite Biomaterials

Abstract: The success or failure of a material when implanted in the body is greatly determined by the surface properties of the material and the host tissue reactions. The very first event that takes place after implantation is the interaction of soluble ions, molecules and proteins from the biological environment with the material surface leading to the formation of an adsorbed protein layer that will later influence cell attachment. In this context, the particular topography and surface charge of a material become cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 40 publications
0
17
0
Order By: Relevance
“…Understanding and manipulating surface charge is critical for most applications involving material-aqueous interfaces, such as protein adsorption, biofilm formation, drug delivery and biodistribution. In the biomaterials context, surface charge at the solid/water interface determines the electrostatic interaction between the biomaterial surface and the soluble ions, molecules and proteins from the biological environment, leading to the formation of an adsorbed protein layer that influences cell adhesion (Espanol, Mestres, Luxbacher, Dory, & Ginebra, 2016). Negatively charged biomaterials are less likely to be internalized by cells than those that are neutral or positively charged when other parameters such as shape and size of the nanoparticles are comparable (L. Chen, McCrate, Lee, & Li, 2011).…”
Section: Surface Charge Analysismentioning
confidence: 99%
“…Understanding and manipulating surface charge is critical for most applications involving material-aqueous interfaces, such as protein adsorption, biofilm formation, drug delivery and biodistribution. In the biomaterials context, surface charge at the solid/water interface determines the electrostatic interaction between the biomaterial surface and the soluble ions, molecules and proteins from the biological environment, leading to the formation of an adsorbed protein layer that influences cell adhesion (Espanol, Mestres, Luxbacher, Dory, & Ginebra, 2016). Negatively charged biomaterials are less likely to be internalized by cells than those that are neutral or positively charged when other parameters such as shape and size of the nanoparticles are comparable (L. Chen, McCrate, Lee, & Li, 2011).…”
Section: Surface Charge Analysismentioning
confidence: 99%
“…Surface zeta potential (SZP) analysis is a vital method for qualifying important features of new materials in technical (e.g., effects of fouling and cleaning of membranes used for water treatment, 3,4 textile industry [5][6][7] ) and biomedical applications (e.g. biolm formation, haemocompatible implants [8][9][10][11] ). Furthermore, it enables to gain insights into modication processes that result from surface treatment or surface interactions with biological or natural environments under near-ambient conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Polarized HA works like a capacitor that charged by applying a high level electric field (kV/mm) at elevated temperature (>200 °C) [15,16,17]. Polarized HA has, in some cases, a positive effect on biological responses, as several studies have reported that the polarized HA exhibited favorable bio-mineralization property and protein adsorption behavior [15,18,19,20,21]. However, its non-piezoelectricity and extremely low depolarization, current density below 200 °C [15] limited its application in environment in vivo.…”
Section: Introductionmentioning
confidence: 99%